RELATIONSHIP BETWEEN DELIVERY METHOD WITH NEONATAL HYPERBILIRUBINEMIA - Jeanette I. Ch. Manoppo; Audrey M.I. Wahani; Ernestine Vivi Sadeli (Jurnal Health Sains, 2023)
Jaundice in newborn was the most leading cause for hospitalization in newborns. It was manifest as yellowish discoloration of mucosa membrane caused by increase in serum or plasma bilirubin. This condition can be cause either by increased production breakdown of red blood cells, disorder in conjugation or impaired excretion. Meanwhile, some research also stated that delivery method can influence bilirubin concentration in newborn. This study was conducted to determine relationship between delivery method with neonatal hyperbilirubinemia that already receive phototherapy.  As much as 104 babies with hyperbilirubinemia were included into this observational research. Around 55% of them, neonates were delivered by caesarean section. In conclusion, caesarean section method of delivery is associated with neonatal hyperbilirubinemia (p value 0.001).